Getting into nursing - Elcock, Karen (London ; Los Angeles : Sage/Learning Matters, 2012)
This book helps applicants to nursing degrees succeed in their applications and pass the numeracy and literacy tests and interviews
1. What is nursing today? -- 2. Do i have what it takes to be a nurse -- 3. Entry requirements -- 4. What is involed in undertaking a nursing degree -- 5. Choosing the right field of nursing -- 6. The application process and choosing the right university -- 7. Preparing for the selection day -- 8. Numeracy tests -- 9. Literacy tests -- 10. The selection day -- 11. What happens next
Includes bibliographical references (p. 139-140) and index
Keywords: Nursing -- Vocational guidance -- Great Britain